An equilibrium analysis on the tripartite evolutionary game of garbage classification recycling - Xu, Lang; Tang, Hui; Liu, Lin; Liu, Liying (Frontiers in Environmental Science, 2023)
The garbage classification recycling policy is proposed to curb the waste of recyclable and land resources, so as to reduce the environmental pollution caused by garbage. In addition, the government and recycling companies are advised to increase the rate at which the evolutionary game model converges to a steady state by reducing their own operating costs during the implementation of garbage classification. On this basis, we also recommend an appropriate increase in the benefits given to citizens, which will have a greatly positive impact on citizens and even also on the government and the recycling companies themselves.